2016
DOI: 10.1016/j.prevetmed.2016.01.012
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of 329 farms in England to identify risk factors for ovine clinical mastitis

Abstract: The aims of this study were to estimate the incidence rate of clinical mastitis (IRCM) and identify risk factors for clinical mastitis in suckler ewes to generate hypotheses for future study. A postal questionnaire was sent to 999 randomly selected English sheep farmers in 2010 to gather data on farmer reported IRCM and flock management practices for the calendar year 2009, of which 329 provided usable information. The mean IRCM per flock was 1.2/100 ewes/year (CI:1.10:1.35). The IRCM was 2.0, 0.9 and 1.3/100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
0
11
0
2
Order By: Relevance
“…Indrebø () has studied specific sheep housing features related to mastitis prevalence and reported higher prevalence rates in sheep houses with slatted floors. However, Cooper, Huntley, Crump, Lovatt, and Green () have reported that concrete and soil were associated with higher incidence rates of clinical mastitis.…”
Section: Non‐animal‐related Predisposing Factorsmentioning
confidence: 99%
“…Indrebø () has studied specific sheep housing features related to mastitis prevalence and reported higher prevalence rates in sheep houses with slatted floors. However, Cooper, Huntley, Crump, Lovatt, and Green () have reported that concrete and soil were associated with higher incidence rates of clinical mastitis.…”
Section: Non‐animal‐related Predisposing Factorsmentioning
confidence: 99%
“…Mastitis, an inflammation of the mammary gland caused by bacterial infection, is characterized by palpable lumps in the udder, abnormal milk, and tissue discoloration in its clinical state ( Menzies and Ramanoon, 2001 ). The average incidence of clinical mastitis ( CM ) is relatively low (1.2% to 3%) across flocks sampled around the world ( Quinlivan, 1968 ; Arsenault et al, 2008 ; Cooper et al, 2016 ), but can have large variation within flocks (0–37%; Grant et al, 2016 ). Nevertheless, CM was the primary reason for culling 6.7% of ewes in the United States in 2011 ( USDA APHIS, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The present study means that good udder conformation or live weight or BCS are not associated with the increase risk of mastitis in Dorper sheep. In contrast, the previous study by [37] indicated that the risk of mastitis infection is associated with udder conformation where the pendulous udder with the extreme teat position and greater cross-sectional area of the teats in dairy ewes resulted increase the risk of mastitis infection in ewes compared to the normal udder conformation [28] also stated that the pendulous udder will make the lamb difficult to suckle effectively and did not feed sufficiently which may trigger the lamb attempt to repeated suckling that could lead to teat lesions or intramammary infection. Moreover, the adjusted R 2 is important value that used in the model for checking their quality of prediction [38].…”
Section: Resultsmentioning
confidence: 63%